Consumer behaviour of senior citizens on the market of goods and services - Bylok, Felicjan (Acta Universitatis Lodziensis. Folia Oeconomica, 2013)
In the paper entitled, the subject matter for analysis was deemed to be the consumer behaviour of the elderly. The author in question attempts to answer the following question: What are the specifics of behaviour for senior citizens on the market of goods and services? What factors determine the consumer behaviour of senior citizens to the largest extent? In the search for answers to these questions, analysis has been run on chosen consumer behavioural features. The factors differentiating the market of goods and services for senior citizen consumers have been presented. There is a concentration on the analysis of the chosen classification by indicating the difficulty in building the typology in this category of purchasers. With the aim of outlining the specifics of the categories of older consumers, the results of self research on the consumer behaviour of senior citizens on the market of goods and services have been presented. The economic, social and individual factors which determine the consumer behaviour of older people have been indicated.